2005
DOI: 10.1111/j.1745-4557.2005.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blanching Method on the Quality Characteristics of Frozen Peas

Abstract: This study evaluated the effects of microwave blanching prior to freezing as an alternative pretreatment for frozen peas. Peas were blanched (steam‐, boiling water immersion‐, microwave‐ or microwave‐blanched in a bag), frozen and evaluated after 0, 6 and 12 weeks for moisture and ascorbic acid content, peroxidase activity, visual appearance and instrumental color, and after 6 and 12 weeks for aroma, flavor and texture. All blanch treatments reduced peroxidase activity by 97% compared with controls (unblanched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 17 publications
(25 reference statements)
3
36
1
3
Order By: Relevance
“…Lin and Brewer (2005) showed, in a study with frozen peas that after microwave and water blanching the peas were also greener. Brewer, Begum, and Bozeman (1995) reported significant darkening of stems and florets of broccoli after microwave blanching.…”
Section: Resultsmentioning
confidence: 95%
“…Lin and Brewer (2005) showed, in a study with frozen peas that after microwave and water blanching the peas were also greener. Brewer, Begum, and Bozeman (1995) reported significant darkening of stems and florets of broccoli after microwave blanching.…”
Section: Resultsmentioning
confidence: 95%
“…However, no such phenomenon occurs during MWB because vegetable tissues can be easily penetrated by internal heat (Lin & Brewer, 2005;Ramesh et al, 2002). Moreover, little water is applied during MWB; therefore, soluble molecules and ions are retained in the tissues of A. bisporus.…”
Section: Effect Of Water Activity On Dielectric Propertiesmentioning
confidence: 99%
“…Hot water blanching (HWB) is mainly used to inactivate enzymes, but it is also used to remove air from the intercellular spaces in fruits and vegetables (Krokida, Kiranoudis, Maroulis, & Marinos-Kouris, 2000;Lin & Brewer, 2005;Ramesh, Wolf, Tevini, & Bognar, 2002). Microwave blanching (MWB) is considered to be superior than conventional blanching because it reduces nutrient loss, shortens drying time, and maintains porosity of dried materials (Kowalska, Lenart, & Leszczyk, 2008;Vadivambal & Jayas, 2007;Walde et al, 2006).…”
mentioning
confidence: 99%
“…Comparative studies reported in literature have not provided enough understanding about the underlying differences between the water and microwave blanching in terms of nutritional value of the frozen products (Bernas & Jaworska, 2003;Lin & Brewer, 2005;Tosun & Yucecan, 2008). Although there are available data in the literature regarding thermal inactivation kinetics of AAO, the residual activity of this enzyme after thermal treatment of broccoli, pumpkin (Cucurbita maxima), carrots (Daucus carota subsp.…”
Section: Introductionmentioning
confidence: 98%